Exploring the influence of urbanization on gut mycobiota through dietary habits in Burkina Faso - Renzi, Sonia; Meriggi, Niccolò; Paola, Monica Di; Bacci, Giovanni; Cerasuolo, Benedetta; Gori, Agnese; Casari, Silene; Banci, Elena; de Blasi, Alessia; Diallo, Salou; Kabore, Berenger; Derra, Karim; et al. (BMC microbiology, 2025)
The phenomenon of urbanization is associated with significant shifts in lifestyle and dietary habits, which can impact the composition of gut microbiota. While variations in gut bacterial communities between rural and urban residents are documented, changes in fungal communities (mycobiota) remain underexplored. This study investigates the impact of urbanization-related dietary shifts on the gut mycobiota in a sub-Saharan African context (Burkina Faso). We analyzed the gut mycobiota composition of individuals from households of rural and semi-urbanized areas, and that of wealthy families living in the capital city (Ouagadougou). We compared the gut mycobiota of three Burkinabè cohorts with that of a cohort of Italian families, as representative of a Western urban lifestyle. Using high-throughput sequencing, we characterized gut mycobiota composition and diversity, assessing changes in accordance with the different dietary patterns and lifestyle. Our findings revealed modifications in gut mycobiota composition along the rural-to-urban gradient. A significant reduction in the alpha-diversity of the gut mycobiota was observed in the cohorts residing in the urban setting compared to those living in rural and semi-urbanized areas. Members of rural households exhibited greater fungal richness and diversity compared to those in urban families, including affluent families in the capital city. Furthermore, we identified 33 fungal amplicon sequence variants (ASVs) significantly associated with the different lifestyle and dietary patterns related to the studied areas. The household-level survey of rural and urban settings in Burkina Faso highlighted the impact of urbanization-related dietary shifts on gut mycobiota diversity and composition. The observed loss of fungal diversity and the significant reduction of fungal taxa associated with a rural lifestyle are potential indicators of the shift from a rural to an urban context. In agreement with the hygiene hypothesis, these findings lay the foundation for further studies aiming at investigating the effect that these microbial losses will have on human health, similarly to those already observed for gut bacterial communities.